Nuclear factor erythroid-2 related factor 2 inhibits human disc nucleus pulpous cells apoptosis induced by excessive hydrogen peroxide - Lin,Hao (2020)
SUMMARY OBJECTIVE Nuclear factor erythroid-2 related factor 2 (Nrf2)/ antioxidant response element (ARE) is a novel defensive pathway involved in the oxidative and chemical stress of cells. The aim of the study was to explore the role of Nrf2 on the apoptosis of human disc nucleus pulpous cells induced by hydrogen peroxide (H2O2). METHODS The degeneration model of human intervertebral disc nucleus pulpous cells was established. The expression of Nrf2 was interfered with using sulforaphane (SFN); for that end, three groups were established: a blank group (H2O2-/SFN-), control group (H2O2+/SFN-), and an experimental group (H2O2+/SFN+). CCK8, Hoechst 33258 living cell staining was used to detect reactive oxygen species (ROS) content. RESULTS The apoptotic rates of the three groups were [(0.40±0.46)%], [(25.98±11.28)%], and [(3.83±2.06)%, respectively. The difference was statistically significant (p<0.05). The relative content of ROS in the three groups was [(100±7)%], [(1538±91)%], and [(818±63)%]; the difference was statistically significant (p<0.05). In Western blotting, Nrf2 content in the experimental group was higher than that in the control group. CONCLUSION Nrf2 exists in the nucleus pulpous cells of human intervertebral discs, which is related to the degeneration of the intervertebral disc. It has negative feedback regulation and can prevent the degeneration of the intervertebral disc by inhibiting the apoptosis of nucleus pulpous cells of human intervertebral discs caused by excessive ROS, which provides a new intervention strategy for the prevention and treatment of the degeneration of intervertebral discs.